Reaksi Pasar pada Ketidaknormalan Pertumbuhan Persediaan - Davyn Muhammad Farrell; Zahroh Naimah (Politeknik Ganesha Medan, 2025)
Abnormal inventory growth may reflect a response to high market demand or indicate inventory manipulation. This study aims to examine the market reaction to abnormal inventory in manufacturing companies in Indonesia. A quantitative approach was employed using an event study method based on secondary data from the financial reports of manufacturing firms listed on the Indonesia Stock Exchange (IDX) for the period 2017–2019. The sample was selected through purposive sampling, and data were analyzed using a one-sample t-test. The results show that a positive market reaction occurred only on the first and second days after the publication of financial statements, as measured by cumulative average abnormal return (CAAR). These findings suggest that abnormal inventory is perceived as good news when interpreted as a signal of the company’s readiness to meet future demand. In contrast, no significant market reaction was observed when abnormal inventory was suspected to result from inventory manipulation. This study contributes to understanding how investors interpret abnormal inventory as a signal of firm performance in the capital market.